The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ol.2017.6472
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of low-intensity pulsed ultrasound sonication on the proliferation of osteosarcoma cells

Abstract: Abstract. To date, there is limited data on the biological effects of low-intensity pulsed ultrasound (LIPUS) on primary malignant bone tumors. The purpose of the present study was to investigate the antitumor effects of LIPUS on osteosarcoma cells. The effects of LIPUS on cell viability, induction of apoptosis, mitochondrial membrane potential and intracellular signaling molecules in the LM8 osteosarcoma cell line were investigated. LIPUS inhibited cell viability (P=0.0022) and mitochondrial membrane potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…LIPUS also inhibits the proliferation of human hepatocellular carcinoma cells and osteosarcoma cells and promotes their apoptosis. 35,36 In this study, LIPUS promoted the proliferation of BMSCs when the cells were exposed to LIPUS for 5 or 10 minutes once a day. However, if BMSCs are irradiated by LIPUS for 20 minutes once a day, 50 mW/cm 2 or higher intensity could inhibit the growth of cells.…”
Section: Discussionmentioning
confidence: 85%
“…LIPUS also inhibits the proliferation of human hepatocellular carcinoma cells and osteosarcoma cells and promotes their apoptosis. 35,36 In this study, LIPUS promoted the proliferation of BMSCs when the cells were exposed to LIPUS for 5 or 10 minutes once a day. However, if BMSCs are irradiated by LIPUS for 20 minutes once a day, 50 mW/cm 2 or higher intensity could inhibit the growth of cells.…”
Section: Discussionmentioning
confidence: 85%
“…Ultrasound can be selectively targeted on tumor cells using focused ultrasound beams and ultrasound may potentially be more toxic to tumor cells due to the higher metabolic rate in glioma cells 10,18. Previous studies showed that ultrasound inhibits cell proliferation in osteosarcoma cells through inhibiting cell viability, mitochondrial membrane potential, reducing phosphorylated mitogen-activated protein kinase 7 and so on 19. In this study, LFLIU inhibited the proliferation of C6 and U87 cells in an intensity-dependent manner, indicates it seems to be an effective and safe procedure in the treatment of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation for 24 h, acrofolione A or B (15 μ m ) was added and the cells were incubated for 24 and 48 h. The collected cells were rinsed with cold PBS and immediately solubilised in cell lysate buffer (Cell Signaling Technology) containing complete protease inhibitor cocktail (Roche Diagnostics Ltd.) and 1 m m phenylmethylsulfonyl fluoride (Sigma‐Aldrich) by blocking the lysates gently at 4 °C for 30 min. The supernatants obtained from microcentrifugation at 14000 g for 5 min were transferred to clean test tubes, the sample proteins (0.5 mg/mL) were diluted and then incubated with PathScan Stress and Apoptosis Signaling Antibody Array kit reagent (Cell Signaling Technology) as per the manufacturer's instructions . The expressed dots were visualised using LumiGlo reagent and detected using an ImageQuant LAS‐4000.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants obtained from microcentrifugation at 14000g for 5 min were transferred to clean test tubes, the sample proteins (0.5 mg/mL) were diluted and then incubated with PathScan Stress and Apoptosis Signaling Antibody Array kit reagent (Cell Signaling Technology) as per the manufacturer's instructions. [23] The expressed dots were visualised using LumiGlo reagent and detected using an ImageQuant LAS-4000. Dot densities were measured using Image J (National Institutes of Health, Bethesda, MD, USA) and corrected to the relative density of a-tubulin.…”
Section: Exploration Of Intracellular Signalling Moleculesmentioning
confidence: 99%